2013
DOI: 10.2176/nmc.53.360
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of Microvascular Decompression Procedures and Patient's Postoperative Quality of Life: Review of 139 Cases

Abstract: Microvascular decompression (MVD) is effective for the relief of symptoms, but little is known about the impact of the MVD procedure on patient's quality of life (QoL) or which QoL factors are important. The surgical results of MVD and the impact of this procedure were evaluated on patient's QoL in 139 patients, 74 with hemifacial spasm (HFS) and 65 with trigeminal neuralgia (TN), who underwent MVD between 2004 and 2011 using the 36-Item Short Form Health Survey questionnaire. Symptoms had resolved in approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…30 As mentioned, the rate of initial pain relief after MVD has been shown to vary from 70% to 100% in patients treated for TN. 1,4,8,12,16,18,29,31,32,34,38 In the largest series, Barker et al reported the results of 1204 MVDs with immediate, 1-year, and 10-year complete pain relief achieved in 82%, 80%, and 70% of procedures, respectively. 4 Sindou et al reported that 73.3% of patients were free of pain at 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 As mentioned, the rate of initial pain relief after MVD has been shown to vary from 70% to 100% in patients treated for TN. 1,4,8,12,16,18,29,31,32,34,38 In the largest series, Barker et al reported the results of 1204 MVDs with immediate, 1-year, and 10-year complete pain relief achieved in 82%, 80%, and 70% of procedures, respectively. 4 Sindou et al reported that 73.3% of patients were free of pain at 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…16 Initial pain relief outcomes for patients undergoing MVD are excellent, ranging from 70% to 100% in multiple studies. 1,4,8,12,16,18,29,31,32,34,38 TN patients commonly undergo multiple less invasive treatment options prior to MVD, but the effect of these prior surgical treatments on the efficacy of subsequent MVD has not been elucidated. Furthermore, few studies have compared the efficacy of MVD performed as first-line surgical intervention to MVD performed as a subsequent surgical intervention, nor has there been examination of factors associated with multiple interventions prior to MVD that predict outcomes.…”
mentioning
confidence: 99%
“…V C 2014 International Parkinson and Movement Disorder Society Key W ords: hemifacial spasm; microvascular decompression; MRI; botulinum toxin; facial nerve Characterized by unilateral hyperactivity of the facial nerve, hemifacial spasm (HFS) can severely reduce a patient's quality of life. [1][2][3][4] Microvascular decompression (MVD), which has been shown to be the most effective therapy for HFS, treats the disease cause by eliminating neurovascular compression. 5,6 The development of higher-resolution magnetic resonance imaging (MRI) pulse sequences and cranial nerve-specific image processing techniques has led to an increased interest in preoperative MRI as a means to detect neurovascular compression.…”
mentioning
confidence: 99%
“…It is suggested that the recovery of a surgery may be influenced by QL factors. TN patients who underwent microvascular decompression (MVD) took almost a year to recover from social and emotional limitations 13 . A short form of this same questionnaire, SF-36 was used to evaluate the long term effect of Gamma Knife Surgery in TN patients.…”
Section: Discussionmentioning
confidence: 99%